Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1093/annonc/mdu524
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous versus intravenous formulation of trastuzumab for HER2-positive early breast cancer: updated results from the phase III HannaH study

Abstract: NCT00950300.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
75
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(90 citation statements)
references
References 5 publications
11
75
0
2
Order By: Relevance
“…Continuing in the development program, there were no cases of severe hypersensitivity reactions, such as anaphylaxis in the pivotal phase 3 HannaH trial comparing SC versus intravenous (IV) trastuzumab formulations. At 12 months median follow-up, only 11% of patients reported injection-site pain, which was predominantly Grade 1 [12], which was further confirmed with the 20-month median follow-up [13]. The Phase 3 SABRINA trial that assessed SC versus IV rituximab with rHuPH20 in combination with chemotherapy also showed that both formulations had similar tolerability; the proportion of patients with Grade 3 or worse AEs or SAEs did not differ between groups [11].…”
Section: Clinical Experience With Rhuph20mentioning
confidence: 53%
See 1 more Smart Citation
“…Continuing in the development program, there were no cases of severe hypersensitivity reactions, such as anaphylaxis in the pivotal phase 3 HannaH trial comparing SC versus intravenous (IV) trastuzumab formulations. At 12 months median follow-up, only 11% of patients reported injection-site pain, which was predominantly Grade 1 [12], which was further confirmed with the 20-month median follow-up [13]. The Phase 3 SABRINA trial that assessed SC versus IV rituximab with rHuPH20 in combination with chemotherapy also showed that both formulations had similar tolerability; the proportion of patients with Grade 3 or worse AEs or SAEs did not differ between groups [11].…”
Section: Clinical Experience With Rhuph20mentioning
confidence: 53%
“…In recent years, the development of rHuPH20 has facilitated subcutaneous administration of monoclonal antibodies such as trastuzumab and rituximab [11][12][13]. In addition, high levels of HA in tumors is associated with treatment resistance to monoclonal antibodies and poor clinical outcomes.…”
Section: Lettermentioning
confidence: 99%
“…Moreover, the neoadjuvant setting allows the use of pCR, which is a better efficacy assessment criterion and is related to survival outcome. [16][17][18] ORR for metastatic lesions is not related to survival outcomes, and has not been used for the basis of any drug registration in breast cancer. 19 Considering these points, the neoadjuvant setting is considered to be an important area for development in HER2-positive breast cancer.…”
Section: Mainmentioning
confidence: 99%
“…17 Trastuzumab has tolerable immunogenicity that does not affect its serum concentration and the pathologic complete response of patients. 18,19 It would be useful to explore whether RabMAbs can be directly humanized by comparison with human sequences, in a similar way to humanization of mouse antibodies. In one study, humanized anti-VEGF RabMAbs have been made by substituting non-critical residues with human residues within both the frameworks and CDR regions.…”
Section: Introductionmentioning
confidence: 99%